The Effects of Working Capital Management on Profitability of Microfinance Institutions in Zambia: A Case Study of Bayport Zambia Limited - Joe Fungai (International Journal of Engineering and Management Research, 2024)
This study investigated the effects of working capital management on the profitability of Bayport Zambia Limited, a microfinance institution in Zambia. The specific objectives were to find out the effect of cash management profitability of Bayport, to assess the effect of non-performing loans (debtors) on Bayport Profitability, to examine the effect of operational expenses on the Profitability of Bayport and to determine the effect of debt recovery effort on the profitability of Bayport. Data were collected through questionnaires and face-to-face interviews with employees and senior management of Bayport Zambia Limited. Descriptive statistics were used to analyse the data, including frequency distribution and percentages. The study found that effective management of liquid cash is crucial for sustaining and maximizing profits. Weak cash management negatively impacts profitability. Managing and mitigating non-performing loans significantly affects financial performance. Weak management of operational expenses can impact profitability. Timely and efficient debt recovery efforts positively influence profitability. Based on these findings, the study makes several recommendations. Bayport should reassess and strengthen debt recovery strategies, reduce high operational expenses, and utilize technology solutions to effectively monitor customer status. Collaboration with regulatory authorities is necessary to develop and enforce a regulatory framework for responsible lending and efficient working capital management. Financial literacy and education programs should be implemented to promote awareness and responsible borrowing. These recommendations aim to improve working capital management and overall profitability in Bayport Zambia Limited and the microfinance sector in Zambia.